2002
DOI: 10.1148/radiol.2242011369
|View full text |Cite
|
Sign up to set email alerts
|

Bone, Muscle, and Fat: Sex-related Differences in Prepubertal Children

Abstract: Together, these data indicate that sex is an important determinant of the morphology in humans well before the beginning of puberty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
45
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 37 publications
13
45
0
1
Order By: Relevance
“…It is base are the Qualitative changes in body composition, which occur at certain stages of girls development and characterized with different relation between the fractions of body mass. Our findings supported these of previous research, which found a different relation between fat, muscle and bone tissue during the different ontogenetic period (1,2,4,11,13,15,17,18,19,22,23,24).…”
Section: Resultssupporting
confidence: 93%
“…It is base are the Qualitative changes in body composition, which occur at certain stages of girls development and characterized with different relation between the fractions of body mass. Our findings supported these of previous research, which found a different relation between fat, muscle and bone tissue during the different ontogenetic period (1,2,4,11,13,15,17,18,19,22,23,24).…”
Section: Resultssupporting
confidence: 93%
“…More recently, these workers [10] have emphasised the importance of measuring fat distribution in children as a method of identifying those at risk from obesity and associated morbidity. Th e present study confi rms the fi ndings of American [1] and European [28,30] researchers that sexual dimorphism of fat patterning in children is present at 5-7 years of age. Our study shows that increased central body fat in girls but former study show that increased central body fat in children is related to adverse changes in lipid profi les [12], insulin metabolism [11] and blood pressure [39].…”
Section: Discussionsupporting
confidence: 87%
“…A tendency towards truncal/central fat distribution in children of prepubertal ages has been reported in the German [28], USA [1] and the Spanish population [30]. Since fat distribution plays a major role in both morbidity and mortality, it is important to examine the nature and timing of fat patterning in children.…”
Section: Introductionmentioning
confidence: 99%
“…Humans experience a brief period of preadolescent growth quiescence preceding the pubertal growth spurt, which corresponds temporally to the initiation of sexual maturation (Arfai et al, 2002;Braillon, 2003). This specific pattern is not observed in rats.…”
Section: Conclusion and Discussionmentioning
confidence: 96%